Unformatted text preview: 2 − 3 D + 10 ) [ y p ( x )] = (34 x − 16) e − 2 x − 10 x 2 + 6 x + 34 ⇒ (34 C x + 17 C 1 − 16 C ) e − 2 x + 10 C 2 x 2 + (10 C 3 − 6 C 2 ) x +10 C 4 − 3 C 3 − 4 C 2 = (34 x − 16) e − 2 x − 10 x 2 + 6 x + 34 . Equating corresponding coeﬃcients, we obtain the system 34 C = 34 , 17 C 1 − 16 C = − 16 , 10 C 2 = − 10 , 10 C 3 − 6 C 2 = 6 , 10 C 4 − 3 C 3 − 4 C 2 = 34 ⇒ C = 1 , C 1 = 0 , C 2 = − 1 , C 3 = 0 , C 4 = 3 . Thus, y p ( x ) = x 2 e − 2 x − x 2 + 3 and y ( x ) = y h ( x ) + y p ( x ) = c 1 e − 2 x + ( c 2 cos x + c 3 sin x ) e 2 x + x 2 e − 2 x − x 2 + 3 371...
View
Full
Document
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Division, Equations, Characteristic polynomial, Complex number, Homogeneity

Click to edit the document details